All Awareness and No Action: Can Social Work Leverage Creative Arts' Potential?. (September 2019) - Travis, Raphael
Social work is grounded with an emphasis on promoting the well-being being of individuals and families with an explicit recognition of how the environment plays a significant role in the unfolding of well-being. Unfortunately, the profession's commitment to maintaining the infrastructure for social work research, education, and practice that helps students and professionals focus on the environmental forces that create, contribute to, and address problems of the living sometimes feels superficial. These trends have made it difficult to realize the effectiveness and promise of integrating creative arts into social work practice. The present article discusses how social work efforts with creative arts will have limited influence if their context, underlying assumptions, and framing are misaligned with the experiential realities of clients; if gatekeeping is too rigid or biased to effectively grow the arts-based infrastructure; and if the underlying assumptions that define well-being outcomes are proportionately narrow, deficit oriented, and short-term focused.